2017
DOI: 10.1111/rec.12501
|View full text |Cite
|
Sign up to set email alerts
|

Tree and bird functional groups as indicators of recovery of regenerating subtropical coastal dune forests

Abstract: Functional diversity indicators are increasingly used to monitor forest function recovery because they connect biodiversity to ecosystem functions. However, identifying which functions deviate from a reference forest has not received much attention, despite its potential to inform restoration interventions. In this study, we used functional groups to assess the recovery of ecosystem functions in regenerating coastal dune forests. We surveyed birds and trees in forest of different ages and a reference old‐growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…These species occur exclusively or preferentially in the forest interior, suggesting that their performance is directly related to tree size and density [4]. However, studies evaluating the responses of bird assemblages to forest restoration generally compare areas in restored vs remnant reference forests [28,29], classify areas in age classes [26,30], or use time since restoration as a continuous predictor variable [31,32]. Although these studies recognize the importance of vegetation structure on bird assemblages, few studies explicitly used the development of forest structure as a predictor variable.…”
Section: Introductionmentioning
confidence: 99%
“…These species occur exclusively or preferentially in the forest interior, suggesting that their performance is directly related to tree size and density [4]. However, studies evaluating the responses of bird assemblages to forest restoration generally compare areas in restored vs remnant reference forests [28,29], classify areas in age classes [26,30], or use time since restoration as a continuous predictor variable [31,32]. Although these studies recognize the importance of vegetation structure on bird assemblages, few studies explicitly used the development of forest structure as a predictor variable.…”
Section: Introductionmentioning
confidence: 99%
“…One group benefiting from the presence of large trees are large frugivores, which are of major importance for long‐distance dispersal and can contribute to restore degraded forest (Galetti et al., ). In the studied rehabilitating forest, previous research has shown a decline in large frugivore abundance as the forest ages (Rolo, Olivier, & van Aarde, ). This evidence is in accordance with the significantly lower presence of tall trees in the rehabilitating forest as compared to the reference forest.…”
Section: Discussionmentioning
confidence: 88%
“…Among wildlife taxa, birds are conspicuous early responders to forest restoration (Dunn 2004, MacGregor-Fors et al 2010, Rolo et al 2017). Because of their diverse life history strategies including wide variation in diet, specialized foraging strategies, and microniche preferences, birds can act as an indicator taxon for recovering ecological complexity during forest restoration (Da Silva and Vickery 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The return of forest-associated birds to forest restorations is a metric of restoration progress (Twedt et al 2002, Nichols and Nichols 2003, Rolo et al 2017. Increasing compositional overlap with forest bird communities at less disturbed reference sites indicates progress toward biodiversity conservation goals (Catterall et al 2012, Rolo et al 2017. In restorations intended as wildlife corridors between forest fragments, forest-associated birds demonstrate restorations are functioning as planned (Jansen 2005).…”
Section: Introductionmentioning
confidence: 99%